Jatropha’s Rapid Developments and Future Opportunities as a Renewable Source of Biofuel—A Review - Asarudheen Abdudeen; Mohamed Y. E. Selim; Manigandan Sekar; Mahmoud Elgendi (Energies, 2023)
Biofuel is an attractive alternative to fossil fuels since it is renewable and biodegradable—it is mainly made from edible and non-edible sources. Globally, the usage of renewable biofuels is expected to rise quickly. The rising production and use of biofuel has prompted an examination of its environmental impact. Biodiesel is a fatty acid methyl ester generated from sustainable lipid feedstock that substitutes petroleum-based diesel fuel. Non-food oils, such as Jatropha, waste cooking oil, and by-products of vegetable oil from refineries provide inexpensive feedstock for biodiesel manufacturing. Due to its increased oil yield, adequate fatty acid content, tolerance to various agro-climatic conditions, and short gestation period, Jatropha may be one of the most promoted oilseed crops worldwide. Furthermore, Jatropha can provide several economic and agronomic advantages because it is a biodegradable, renewable plant. This study examines whether Jatropha can be considered as the most preferable biofuel in the future. The study begins with an overview of current fuels, including their classifications, dynamic changes in consumption, advantages, and cross-examining the limitations to identify the significance of bringing an alternate fuel. Then we elaborate on the outlook of the Jatropha crop, followed by evaluating its availability, opportunity, and advantages over other biofuels. Subsequently, the extraction methods, including the transesterification process and integration methods for improving the efficiency of Jatropha fuel, are also reviewed in the paper. We also assess the current stage of Jatropha cultivation in different countries with its challenges. The review concludes with future perspectives and directions for research.